Evaluation of Mean Platelet Volume and Other Complete Blood Count Parameters in Children with Atopic Asthma - Dilek GİRAY; Mehmet ÖZDEMİR (Bezmiâlem Science, 2018)

(untitled)
Objective:Allergic diseases are increasing in developed countries. Recent studies show that platelets (PLTs) may also be responsible for the development of allergies. The aim of the present study was to investigate whether allergic diseases are related to the levels of mean platelet volume (MPV) and other complete blood count (CBC) parameters.Method:In the present study, 337 pediatric patients (aged 2-18 years) who were admitted to the pediatric allergy clinics with a diagnosis of atopy, which was supported with the positivity of at least one skin prick test and/or total IgE and/or allergen-specific IgE, were included. The results of the patients including MPV and other CBC parameters and total IgE values were compared with 120 healthy sex and age-matched children.Results:There was no difference in hematocrit counts between the groups, but the hemoglobin level was higher in patients. The mean corpuscular volume was lower in the study group, which was not statistically significant. The white blood cell count and thrombocyte count of the patients were higher than those of the controls, but were not statistically significant. The MPV values were significantly lower in the patient group. There was a negative correlation between the MPV values and the thrombocyte counts in the study group. Finally, the MPV values were significantly higher in patients ≥6 years and females in the study group.Conclusion:PLTs cause inflammation by secreting mediators in children with allergy. When the thrombocyte count increases, the MPV decreases reversely. Thus, the MPV may be an effective and inexpensive indicator in the process of inflammation, but long-term studies are needed to evaluate asymptomatic and exacerbation periods.